Detection of L.Monocytogenes in animal and water samples in Kubah National Park, Kuching, Sarawak - Aimi Syazana, Anuar (Universiti Malaysia Sarawak (UNIMAS), 2012)
Listeria monocytogenes (L. monocytogenes) is facultative anaerobic pathogens that can asymptomatically infect various animals. Normally, it also can be found in environment such as vegetation, water, soil, dust, mud and sewage. This study was conducted to detect the presence of L. monocytogenes and antimicrobial susceptibility characteristic from wildlife and water samples at Kubah National Park, Kuching. Samples collected were incubated and streaked on selective medium P ALCAM agar to confirm the presence of Listeria spp. before they were further tested using biochemical and molecular analysis. Specific Polymerase Chain Reaction (PCR) assay were performed to target specific virulence gene, such as haemolysin gene, h/yA to further distinguish the presence ofthis pathogenic bacteria in the sample. The h/yA gene plays major roles in haemolytic properties in L. monocytogenes as it produces Listeriolysin 0 (LLO) which involve actively in lysis process of phagocytic membrane by releasing pore-forming toxin. Overall, out of the 30 samples tested, 10 samples were confirmed as to contain L. monocytogenes isolates and selected to subsequent antimicrobial susceptibility test. The test revealed that 90010 of the isolates were resistant to Tetracycline (30 ~g) and Erythromycin (30 Jlg) while Gentamycin (10 Jlg) and Tobramycin (10 Jlg) has the lowest level of resistance (0%). The mUltiple antibiotic resistances shown by L. monocytogenes isolates in this study indicate the potential health hazard associated with the possible transmission between wildlife and water to its surrounding environment especially visitors of Kubah National Park, Kuching